Cross Culture Generasi Milenial dalam Film “My Generation” - Sigit Surahman; Meliana Pratiwi; Annisarizki Annisarizki (Institut Seni Indonesia Yogyakarta, 2019)
This research aims to explore the signs that represent the millennial generation cross culture in the film My Generation (2017) by Upi Avianto. This film, shows the dynamics of life for generations of millennials in the era of technological development. Unlike teen films in general, this film dares to portray the reality of a teenager's life from the results of two years of director research through social media. So that the film portrays the cross-culture of the millennial generation with what is positive and negative. With Roland Barthes's semiotic analysis method and qualitative descriptive approach and constructivist paradigm. The theory used by researchers is the Representation theory of Stuart Hall. From this research shows the millennial cross culture is represented by various scenes that describe habits and characters that are different from the previous generation. Millennial generation's cross culture is shown in differences in social norms which do not care about politeness values, millennial generation stereotypes, differences in life perspectives that tend to be free or liberal, broader, open and courageous to show differences, and a strong and optimistic mindset.